Decreasing motor stereotypy in individuals with autism spectrum disorder: A systematic review. (September 2020) - Akers, Jessica S.; Davis, Tonya N.; Gerow, Stephanie; Avery, Suzannah
Highlights: We analyzed data from 71 studies that targeted reductions in motor stereotypy. The most common form of motor stereotypy was hand and finger stereotypy. Antecedent interventions were the most commonly implemented interventions. The interventions were more frequently implemented in therapy and school settings. Abstract: Background: Stereotypic behaviors are repetitive, coordinated, seemingly purposeless behaviors that are most often maintained by automatic reinforcement. Motor stereotypy can range from mild to severe depending on the topography, frequency and extent to which they interfere with ongoing activities. Individuals with autism spectrum disorder (ASD) are at an increased risk of exhibiting complex motor stereotypies. Method: The purpose of this literature review was to summarize and evaluate the quality of the literature on behavioral interventions to reduce motor stereotypy among individuals with ASD. We reviewed 126 experiments that addressed motor stereotypy using antecedent interventions, reinforcement-based interventions, punishment interventions or a combination of interventions. Results: We determined that altering the environment during the session (e.g., continuous access to a competing stimulus) and differential reinforcement of alternative behavior are evidence-based interventions according to the What Works Clearinghouse standards. Conclusions: Based on these findings, we discuss considerations for implementing these interventions, procedures for conducting assessments, and areas for future research.